Perception of Kazakhstan as a tourist destination - Tleuberdinova, A.T.; Shayekina, Zh.M.; Salauatova, D.M.; Torzhanova, D.A. (BUKETOV BUSINESS REVIEW, 2017)
In today's tourism business, where the majority of the destinations are almost identical on most criteria, the need for a unique identifier of the destinations to differentiate the services in a variety of existing competitors becomes more important than ever. The authors of this article analyze the image of Kazakhstan as a tourist destination based on the survey of foreign Kazakh expert views in order to promotea better perception of the country through a single serial communications program to improve and maintain the personification by concerned parties. The findings make it possible to determine the branding strategy of the country as a tourist destination. Article is published using the funds of grant of the research project «Theoretical and practical bases of the Republic of Kazakhstan brand formation as a factor for long-term development of the tourism industry».